Immediate implant placement and provisionalization of maxillary anterior single implants. Issue 1 (25th February 2018) - Kan, Joseph Yun Kwong; Rungcharassaeng, Kitchai; Deflorian, Matteo; Weinstein, Tommaso; Wang, Hom‐Lay; Testori, Tiziano
Abstract: An inevitable loss of soft and hard tissue after tooth extraction often results in a compromised site for anterior implant esthetics in both vertical and horizontal dimensions. Immediate implant placement and provisionalization has been a viable option for replacing failing maxillary anterior teeth as it preserves the vertical existing osseous and gingival architecture. With the simultaneous addition of soft‐ and hard‐tissue grafts, the peri‐implant horizontal tissue topography can also be maintained. The esthetic success of immediate implant placement and provisionalization procedures is influenced by a number of factors that can be identified as patient‐dependent or clinician‐dependent. This article describes in detail the process of patient selection, indications, contraindications, diagnosis, treatment planning and treatment execution required to achieve functional and esthetic success with immediate implant placement and provisionalization.